Electrical Conductivity and Morphology Study of Polyaniline Powder Synthesised with Various Doping Ions - S. Golba; M. Popczyk; S. Miga; J. Jurek-Suliga; M. Zubek (Archives of Metallurgy and Materials, 2019)
Powdered polyaniline (PANI) was synthesised chemically with different doping anions namely hydrochloric acid, sulphuric acid and para-toluenesulfonic acid (pTSA). Two-step synthetic procedure was utilised at low temperature. The highest reaction efficiency was found for chlorine-doped PANI. Structural characterization with FTIR revealed the vibration bands characteristic to formation of the emeraldine salt. The surface morphology of doped PANIs was studied by SEM images which showed near globular shape and porous structures with different size of the aggregated particles. They were smaller for Cl–- or pTS–-doped PANI while for SO42– the size was markedly larger. The XRD patterns revealed that there are ordered regions especially for pTS– doped PANI, while the highest conductivity value was recorded for Cl– doped one followed by organic pTS– doped and SO42– doped one.